Leadership style towards organization commitment of non-executive employees at Tenaga Nasional Berhad Negeri Johor / Muhamad Zarif Roslan and Ain Najwa Kamal - Roslan, Muhamad Zarif; Kamal, Ain Najwa (Faculty of Business and Management, 2013)
This research has been conducted to identify the relationship between leadership style and organization commitment. This research also has identified which is the most dominant leadership style toward the organization commitment. This research has been conducted for 150 respondents which include non-executive employees of Tenaga Nasional Berhad Negeri Johor which included all branches in Johor. Data collected have been analysed by using Statistical Package for Social Science (SPSS) Version 2.0. Descriptive analysis has been used to identify demography respondent, leadership style and organization commitment of non-executive employees have been used. Pearson Correlation has used to determine the relationship between leadership style and organization commitment and which is the most dominant towards the organization commitment. Multiple Regression analysis has been used to analyze which leadership style is the most dominant towards the organization commitment. Result of this research have identify that transformational leadership style is the most highly practiced in TNB Johor. Same goes to the most dominant leadership style is the transformational leadership style towards the organization commitment. Transformational, transactional and laissez-faire have positive relationship with the organization commitment too.